The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7ta05171a
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylbenzyl chloride)-based poly(ionic liquids) as membranes for CO2 capture from flue gas

Abstract: Poly(ionic liquid)-based thin film composite membranes capture carbon dioxide from mixed gas streams imitating flue gas separations under various process conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 74 publications
1
47
0
Order By: Relevance
“…However, their CO 2 /N 2 selectivity is less than 31 at 35 °C owing to the physical aging of the polymers. Nikolaeva et al . prepared thin PILMs with post‐modification of commercial polyvinylbenzyl chloride (PVBC) by employing a solvent casting method.…”
Section: Co2 Capture and Separation By Ionic Liquids‐based Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their CO 2 /N 2 selectivity is less than 31 at 35 °C owing to the physical aging of the polymers. Nikolaeva et al . prepared thin PILMs with post‐modification of commercial polyvinylbenzyl chloride (PVBC) by employing a solvent casting method.…”
Section: Co2 Capture and Separation By Ionic Liquids‐based Membranesmentioning
confidence: 99%
“…However, their CO 2 /N 2 selectivity is less than 31 at 35°C owing to the physical aging of the polymers. Nikolaeva et al [66] prepared thin PILMs with post-modification of commercial polyvinylbenzyl chloride (PVBC) by employing a solvent casting method. (Figure 5a) They demonstrated that the intrinsic material properties of PILs was determined by ion asymmetry and the presence of polar alkyl groups.…”
Section: Ionic Liquid-derived Poly(ionic Liquid)s Based Membranes (Pimentioning
confidence: 99%
“…[22] Poly(ionic liquids) (PILs), polymers derived from monomers basedo nI Ls,h ave also been investigated for CO 2 capturing. [23][24][25][26] PILs are ionically conductive and their CO 2 adsorption capacity is between 2a nd 20 mg g À1 ,which is higher than their IL counterparts. [2,[27][28][29][30][31] Managing carbon dioxide (CO 2 )r eleased from large-scale industrialp rocesses is of great importance,y et there remain significant technical challenges.H erein, the fabrication of 1mm-thicks olid-state electrochemical devices based on poly-(ionic liquid) ionogels with embedded electrodes capable of both adsorption and electrochemical reduction of CO 2 is reported.T he ionogelsa re prepared via radical polymerization and chemical crosslinking of avinyl imidazolium trifluoromethanesulfonimide ionic liquid monomer in the presence of additional ionic liquids (ILs) that act as swellinga gents and enhance ionic conductivity.…”
Section: Introductionmentioning
confidence: 96%
“…However, these systems can only operate at low pressures in order to prevent IL loss during the recovery and separation process . Poly(ionic liquids) (PILs), polymers derived from monomers based on ILs, have also been investigated for CO 2 capturing . PILs are ionically conductive and their CO 2 adsorption capacity is between 2 and 20 mg g −1 , which is higher than their IL counterparts …”
Section: Introductionmentioning
confidence: 99%
“…The separation of carbon dioxide (CO 2 ) from other light gases is a process with considerable attention of researchers in industry and academia . Since membrane technology has several prominent properties such as low energy consumption, low capital investment, and simple operations, it is one of the well‐known energy‐efficient and economical techniques for gas separation applications . Separation through membranes is dominated by diffusivity and solubility of permeating materials in membranes.…”
Section: Introductionmentioning
confidence: 99%